2019
DOI: 10.1186/s12889-018-6310-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the perceived stress scale in Ethiopian university students

Abstract: BackgroundStress is a common psychological condition usually associated with many psycho-physical disorders. Stress and its risk factors are frequently seen in Ethiopians including university students. In such circumstances, a valid measure to screen for stress in Ethiopians is necessary. Therefore, we assessed the psychometric properties of the Perceived Stress Scale (PSS) in Ethiopian university students.MethodsA cross-sectional study with a simple random sampling method was performed on students of Mizan-Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 30 publications
4
65
0
Order By: Relevance
“…We used the perceived stress scale that is validated in Ethiopia [33], composed of 10 items each with five possible responses, and the overall value of a scale ranges from zero to 40.…”
Section: Data Collection Instruments and Proceduresmentioning
confidence: 99%
“…We used the perceived stress scale that is validated in Ethiopia [33], composed of 10 items each with five possible responses, and the overall value of a scale ranges from zero to 40.…”
Section: Data Collection Instruments and Proceduresmentioning
confidence: 99%
“…PSS had an internal consistence of Cronbach's alpha for the total score of PSS = 0.793 [38]. Even though it is not directly on epileptic patients, PSS is validated among Ethiopian university students [39].…”
Section: Data Collection Instruments and Proceduresmentioning
confidence: 99%
“…[27][28][29][30] Several past studies have examined the validity of PSS-10 to assess perceived stress among university students. [31][32][33][34][35][36][37] For example, a previous study examined confirmatory factor analysis (CFA) of PSS-10 and they found the 2-factor model is most suitable to assess perceived stress among the Ethiopian university students. 31 Similarly, another study evaluated the principal components factor analysis of PSS-10 and they reported an adequate reliability and validity of PSS-10 to measure perceived stress among Turkish university students.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] For example, a previous study examined confirmatory factor analysis (CFA) of PSS-10 and they found the 2-factor model is most suitable to assess perceived stress among the Ethiopian university students. 31 Similarly, another study evaluated the principal components factor analysis of PSS-10 and they reported an adequate reliability and validity of PSS-10 to measure perceived stress among Turkish university students. 32 Additionally, Lu et al 34 conducted construct validity analysis of PSS-10 and they reported that the 2-factor model of the principal component analysis indicated positive (Factor 1) and negative (Factor 2) perception of stress among Chinese university students.…”
Section: Introductionmentioning
confidence: 99%